Emulsifiers in food technology - Norn, Viggo (Wiley Blackwell, 2015)
Emulsifiers are essential components of many industrial food recipes. They have the ability to act at the interface between two phases, and so can stabilise the desired mix of oil and water in a mayonnaise, ice cream or salad dressing. They can also stabilise gas/liquid mixtures in foams. More than that, they are increasingly employed in textural and organoleptic modification, in shelf life enhancement, and as complexing or stabilising agents for other components such as starch or protein. Applications include modifying the rheology of chocolate, the strengthening of dough, crumb softening an.